Publisher Correction to: A Microscopic Model for a One Parameter Class of Fractional Laplacians with Dirichlet Boundary Conditions - Bernardin, Cèdric (2021)
Due to typesetting mistakes, in equations 2.1 and 2.6 the 1 was incorrect. On page 17, the second equation of Theorem 3.2 was incorrect. The original article has been corrected.